2007
DOI: 10.1002/bit.21730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shear on performance and microbial ecology of continuously stirred anaerobic digesters treating animal manure

Abstract: We determined the effect of different mixing intensities on the performance, methanogenic population dynamics, and juxtaposition of syntrophic microbes in anaerobic digesters treating cow manure from a dairy farm. Computer automated radioactive particle tracking in conjunction with computational fluid dynamics was performed to quantify the shear levels locally. Four continuously stirred anaerobic digesters were operated at different mixing intensities of 1,500, 500, 250, and 50 revolutions per min (RPM) over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(83 citation statements)
references
References 33 publications
3
75
3
2
Order By: Relevance
“…The manure was blended to facilitate the feeding of the digesters, although this assay showed that the blending consisted in a form of pretreatment that increased the methane production of the manure by 46%. Nevertheless, the methane produced from the manure only assays were in the same range as what is generally presented in the literature for manure anaerobic digestion [27,28]. The replacement of 20% of the manure by switchgrass (wet weight) in the assay yielded 32% more methane, although the gain was 92% if compared with the raw manure.…”
Section: Methane Potential Assayssupporting
confidence: 66%
“…The manure was blended to facilitate the feeding of the digesters, although this assay showed that the blending consisted in a form of pretreatment that increased the methane production of the manure by 46%. Nevertheless, the methane produced from the manure only assays were in the same range as what is generally presented in the literature for manure anaerobic digestion [27,28]. The replacement of 20% of the manure by switchgrass (wet weight) in the assay yielded 32% more methane, although the gain was 92% if compared with the raw manure.…”
Section: Methane Potential Assayssupporting
confidence: 66%
“…However, it has also been recommended by some researchers to avoid intense stirring during the start-up phase Stroot et al, 2001;Hoffmann et al, 2008). To clarify these arguments, this experiment compared vigorously stirred and unstirred reactors during the start-up phase.…”
Section: The Effect Of Stirring During the Initial Start-up Periodmentioning
confidence: 99%
“…There was a tendency that the abundance of the Methanosaeta showed a marked increase when mixing speed was low (50-60 rpm) or minimal rather than high [29,30]. In this study, the CMR was stirred at 300 rpm and equipped with the impellor twice the diameter of the other researches [29,30]. The strong mixing in the CMR may have negatively affected the growth of the Methanosaeta.…”
Section: Microbial Community Structure Responsible For Methane Generamentioning
confidence: 85%
“…Another possible factor governing the methanogenic community is the mixing condition [29,30]. There was a tendency that the abundance of the Methanosaeta showed a marked increase when mixing speed was low (50-60 rpm) or minimal rather than high [29,30]. In this study, the CMR was stirred at 300 rpm and equipped with the impellor twice the diameter of the other researches [29,30].…”
Section: Microbial Community Structure Responsible For Methane Generamentioning
confidence: 97%
See 1 more Smart Citation